Fast consolidation and properties of a nanostructured AlCr2–2Al2O3 composite from mechanochemically synthesized powders by pulsed current activated heating. Issue 5 (April 2016) - Kwak, Bong-Won; Shon, In-Jin
Abstract: Nanopowders of AlCr2 and Al2 O3 were fabricated using high-energy ball milling. Dense nanostructured AlCr2 –2Al2 O3 composite was sintered by pulsed current activated heating within 2 min, from mechanically synthesized powders. The advantage of this process is that it allows very quick densification to near-theoretical density and prohibition of grain growth in nanostructured materials. Highly dense AlCr2 –2Al2 O3 composite with a relative density of up to 97% was produced under application of an 80 MPa pressure with the pulsed current. The fracture toughness of the AlCr2 –2Al2 O3 composite of this study is similar to that of a previous study and its hardness is higher due to the grain refinement. The fracture toughness of the AlCr2 –2Al2 O3 composite is higher than that of pure Al2 O3 .